Exploration Media of Muhammadiyah University of Sidoarjo with Mixed Reality - Aswin Damardono; Irwan Alnarus Kautsar (JOINCS (Journal of Informatics, Network, and Computer Science), 2020)
Mixed reality technology is a combination of Augmented Reality (AR) and Virtual Reality (VR) technology. Augmented reality and virtual reality are often used for various fields in terms of education, media promotion, even used as games to make it more interesting, creative and innovative. With the existence of these two advanced technologies, the advertising media as well as promotion and entertainment media really need this kind of technological innovation in introducing the media one step further with technology. Mixed Reality can be used to make it easier for prospective students or the public to explore campuses at the University of Muhammadiyah Sidoarjo through the virtual world without having to come to the location. For this reason, the contribution of this research is to provide alternative digital information media services and access to information available at the Muhammadiyah University of Sidoarjo as a means of educating the campus community on the community and the academic community.